2015
DOI: 10.1111/1462-2920.13037
|View full text |Cite
|
Sign up to set email alerts
|

Species coexistence in simple microbial communities: unravelling the phenotypic landscape of co‐occurring Metschnikowia species in floral nectar

Abstract: Identifying the ecological processes that underlie the distribution and abundance of species in microbial communities is a central issue in microbial ecology and evolution. Classical trade-off based niche theories of resource competition predict that co-occurrence in microbial communities is more likely when the residing species show trait divergence and complementary resource use. We tested the prediction that niche differentiation explained the co-occurrence of two yeast species (Metschnikowia reukaufii and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 62 publications
2
23
0
Order By: Relevance
“…However, we found no significant correlation between geographic and genetic distance, in contrast to previous studies indicating that dispersal limitation may be important (Herrera et al., ). Likewise, although the large differences we found in the growth rates of the genotypic groups are consistent with previous work (Pozo et al., ), the phenotypic characteristics of the strains we measured did not explain the observed patterns of strain abundance and distribution well, suggesting that environmental sorting may not adequately explain the patterns for the populations we studied here. Instead, our adaptive evolution modelling suggested that the three genotypic lineages might have evolved under different selective pressures in terms of the ecologically relevant trait, μ nectar , possibly towards fitness optima that might be diverging across the lineages.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…However, we found no significant correlation between geographic and genetic distance, in contrast to previous studies indicating that dispersal limitation may be important (Herrera et al., ). Likewise, although the large differences we found in the growth rates of the genotypic groups are consistent with previous work (Pozo et al., ), the phenotypic characteristics of the strains we measured did not explain the observed patterns of strain abundance and distribution well, suggesting that environmental sorting may not adequately explain the patterns for the populations we studied here. Instead, our adaptive evolution modelling suggested that the three genotypic lineages might have evolved under different selective pressures in terms of the ecologically relevant trait, μ nectar , possibly towards fitness optima that might be diverging across the lineages.…”
Section: Discussionsupporting
confidence: 85%
“…Moreover, dispersal and environment can have interactive, not just additive, effects on populations. In nectar‐inhabiting yeasts, for example, local coexistence of populations has been attributed to resource use, in combination with plant host‐mediated phenotypic differences among strains (Pozo et al., ). However, resource competition can be strong among these yeasts, and the outcome of competition can depend on the order in which different strains disperse to flowers (Peay, Belisle, & Fukami, ), potentially obscuring the matching of phenotype and environment.…”
Section: Introductionmentioning
confidence: 99%
“…Despite significant variation across floral organs, and potential effects of microbes of anthers, pollen, styles and stigma on direct fitness effects (not mediated by pollinators), most studies of microbial communities associated with flowers have concerned microbes of nectar (e.g., Belisle et al, ; Herrera et al, ; Mittelbach, Yurkov, Stoll, & Begerow, ; Pozo et al, ; Vannette & Fukami, ). These studies have shown the importance of pollinators in shaping some of the assembly patterns of these microbiomes (Belisle et al, ; Herrera et al, ; Vannette & Fukam, ).…”
Section: Introductionmentioning
confidence: 99%
“…Nectar is a ubiquitous resource not just for pollinating animals, but also for the microbes that are introduced via pollinators [13]. A small number of yeast and bacterial species, which comprise the nectar microbiome, can tolerate the osmotic pressure caused by high sugar concentrations and the nutritional scarcity caused by low amino acid concentrations [13,14]. Recent studies show that these species engage in resource competition, resulting in strong and pervasive priority effects [10,11].…”
Section: Introductionmentioning
confidence: 99%